TRANSFORMATION OF NATIONAL VALUES IN TRADITIONAL SINGING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the preservation, development, and renewal of national values in traditional singing under contemporary conditions. The study examines how the spiritual views, aesthetic taste, moral principles, and artistic thinking of the Uzbek people are expressed through maqom, katta ashula, folk songs, and classical performance traditions. In traditional singing, national values are interpreted not merely as historical heritage, but as a living cultural process that is continuously renewed in accordance with the demands of time. Based on the views of Uzbek music scholars, composers, and performers such as Yunus Rajabiy, Abdurauf Fitrat, O. Matyoqubov, I. Rajabov, S. Mannopov, and T. Qodirov, the article reveals the educational, aesthetic, and performance potential of traditional singing. The results of the study show that traditional singing is an important means of transmitting national values from generation to generation and harmonizing them with modern performance, education, and stage culture.